Recommendations for individual participant data meta-analyses on work stressors and health outcomes: comments on IPD-Work Consortium papers - BongKyoo Choi; Peter Schnall; Paul Landsbergis; Marnie Dobson; Sangbaek Ko; Viviola Gómez-Ortiz; Arturo Juárez-Garcia; Dean Baker (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
The IPD-Work (individual-participant data meta-analysis of working populations) Consortium has published several papers on job strain (the combination of low job control and high job demands) based on Karasek's demand-control model (1) and health-related outcomes including cardiovascular disease (CVD), cancer, obesity, diabetes as well as health-related behaviors, utilizing meta-analyses of a pooled database of study participants from 17 European cohorts. An IPD approach has some advantages over typical meta-analyses, eg, having access to all the data for each individual allows for additional analyses, compared to typical meta-analyses. However, such an approach, like other meta-analyses, is not free from errors and biases (2-6) when it is not conducted appropriately. In our review of the IPD-Work Consortium's (hereafter called the Consortium) publications of the last two years, we have identified and pointed out several conceptual and methodological errors, as well as unsubstantiated conclusions and inappropriate recommendations for worksite public health policies (6-15). However, the Consortium has not yet appropriately addressed many of the issues we have raised. Also several major errors and biases underlying the Consortium IPD meta-analysis publications have not been presented in a comprehensive way, nor have they been discussed widely among work stress researchers. We are concerned that the same errors and biases could be repeated in future IPD Consortium meta-analysis publications as well as by other researchers who are interested in meta-analyses on work stressors and health outcomes. It is possible that the inappropriate interpretations in the Consortium publications, which remained uncorrected to date, may have a negative impact on the international efforts of the work stress research community to improve the health of working populations. Recently, Dr. Töres Theorell, a principal investigator of the Consortium, responded in this journal (16) to some of our criticisms on the Consortium papers (17, 18). The purpose of this article is to discuss the methodological and substantive issues that remain to be resolved and how they could be addressed in future analyses. We provide recommendations for future IPD or typical meta-analyses on work stressors and health outcomes. Finally, we discuss the inappropriate conclusions and recommendations in the Consortium publications and provide alternative recommendations, including a comprehensive perspective on worksite intervention studies.